EATING AND NUTRITION EDUCATION AS SOCIAL PRACTICE - Hayda Alves; Patrícia Walker (Universidade do Estado do Rio de Janeiro, 2013)
EDUCAÇÃO EM NUTRIÇÃO: INTEGRANDO EXPERIÊNCIAS Maria Cristina Faber Boog. 1ª ed., Campinas: Komedi Editora, 2013. 268 p. ISBN: 9788575826775 The book Educação em Nutrição: integrando experiências (Education in Nutrition: binding experiences), by Maria Cristina Faber Boog, deals with the topics of eating and nutrition within the scope of health interventions as educational practice, transforming social reality, besides focusing in the individual and on collectivity.